Level of Difficulty Using Verbs Meaning ``To Wear" in Sentences by Students of the Japanese Language Education Study Program - Aror, Susanti; F. Lensun, Sherly; Sompotan, Amelia; Pandi, Helena (KnE Social Sciences, 2024)
Verbs with the meaning ’to wear’, have functions and rules of use. Even though they have the same meaning, namely “to wear” in Indonesian, in Japanese the verb “to wear” varies depending on the object used. This is different from the verb “wearing” in Indonesian, which is the same when used on different objects. The formulation of the problem in this study is: (1) How is the ability to use the verb to wear in Japanese sentences by Semester II Students of PBJ FBS UNIMA Study Program? (2) What verbs are difficult for Semester II students of PBJ FBS UNIMA in using the verb wear in Japanese sentences? The method used in this research was descriptive. The results showed: (1) the average mastery of the verb to wear by Semester II Students of PBJ FBS UNIMA Study Program was divided into two large groups. The group that is categorized as “capable” is 40% and “poor” is 48%, while those who were unable are only 12%. The standard assessment criteria were judged based on the difficulty level of the question. There were 10 students who were able to use the verb to wear with a percentage of 40%, there were 12 students who were less able to use the verb to wear with a percentage of 48%, and there were 3 people who were unable to use the verb to wear with a percentage of 12%. (2) Based on the results of research tests on the level of difficulty of the questions, it was found that the verbs considered difficult were the verbs tsukemasu (つけます), shimasu (します), makimasu (まきます), and hamemasu (はめます). Keywords: verbs, language, Japanese, education, sentence